2002
DOI: 10.1046/j.1440-1746.2002.02662.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic covalent adduct formation with zomepirac in the CD26‐deficient mouse

Abstract: These data definitively showed that CD26 was a component of ZP-modified proteins in vivo. In addition, the data suggested that at least one other protein of approximately 110 kDa was modified by covalent adduct formation with ZAG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…Using TR-rats, deficient in the transporter Mrp2, which transports glucuronides across the canalicular membrane, they were able to show that when diclofenac-glucuronide transport into the bile was absent, no formation of the 118 kDa adduct was seen, thus demonstrating the need for biliary transport of the glucuronides, and subsequent increased concentration of diclofenac-glucuronide in bile [82] . Similar covalent binding to DPP IV has been shown for zomepirac [83,84] and benoxaprofen [73] .…”
Section: Consequences Of Chemical Reactivity Of Carboxylic Acid Metabsupporting
confidence: 69%
“…Using TR-rats, deficient in the transporter Mrp2, which transports glucuronides across the canalicular membrane, they were able to show that when diclofenac-glucuronide transport into the bile was absent, no formation of the 118 kDa adduct was seen, thus demonstrating the need for biliary transport of the glucuronides, and subsequent increased concentration of diclofenac-glucuronide in bile [82] . Similar covalent binding to DPP IV has been shown for zomepirac [83,84] and benoxaprofen [73] .…”
Section: Consequences Of Chemical Reactivity Of Carboxylic Acid Metabsupporting
confidence: 69%
“…Like those of diclofenac, these included adducts of DPPIV, a glycoprotein expressed on the bile canalicular surface, and their formation was apparently mediated through biliary excretion of zomepirac acyl glucuronide 181. Further evidence for the role of DPPIV in zomepirac adduct formation comes from studies on the CD‐26 deficient mouse 182. Depletion of DPPIV (CD26) from deficient mice decreased levels of adduct formation.…”
Section: The Inherent Reactivity Of Acyl Glucuronidesmentioning
confidence: 99%
“…Depletion of DPPIV (CD26) from deficient mice decreased levels of adduct formation. The detection of residual zomepirac adducts in the CD‐26 deficient mouse suggested that proteins of a similar molecular weight to DPPIV may also be targets for zomepirac adduction 182. Antibody methods do not provide conclusive proof that adducts are formed from acyl glucuronide metabolites, as they only recognise the parent drug residue, and, as with tolmetin, zomepirac forms oxidised metabolites which may themselves modify proteins 183–185.…”
Section: The Inherent Reactivity Of Acyl Glucuronidesmentioning
confidence: 99%
“…Both ZP and TM acyl glucuronides have been shown to be capable of covalently modifying proteins via the glycation mechanism (Smith et al, 1986(Smith et al, , 1990Hyneck et al, 1988). Target proteins for modification include plasma albumin in humans, tubulin and dipeptidyl peptidase IV in rats, and CD26 in mice (Bailey et al, 1998;Wang et al, 2001Wang et al, , 2002. As a result, the reactive acyl glucuronides of ZP and TM have been hypothesized to serve as mediators of the serious adverse effects of these drugs (Zia-Amirhosseini et al, 1995).…”
mentioning
confidence: 99%